Sports-related concussion: ongoing debate - Slobounov, S.; Bazarian, J.; Bigler, E.; Cantu, R.; Hallett, M.; Harbaugh, R.; Hovda, D.; Mayer, A. R.; Nuwer, M. R.; Kou, Z.; Lazzarino, G.; Papa, L.; et al. (British Journal of Sports Medicine, 2014)
Research in mild traumatic brain injury (mTBI), also known as concussion, has increased significantly within the past decade parallel to the increased attention being given from injured athletes on high school, collegiate and professional sports teams. These patients have focused the research community's efforts into further understanding the pathophysiological underpinnings of the injury as well as its both short-term and long-term effects. Widespread media coverage and several high-profile cases have raised the issue of possible severe and devastating long-term consequences of repetitive sports-related brain trauma that may involve the acquisition of a proteinopathy as well as an increased risk for developing neurodegenerative diseases associated with repetitive concussive and subconcussive blows. Following a concussive episode there is a destructive pathophysiological and biochemical response that initiates a chain of neurometabolic and neurochemical reactions that include activation of inflammatory response, imbalances of ion concentrations, increase in the presence of excitatory amino acids, dysregulation of neurotransmitter synthesis and release, imbalance in mitochondrial functions and energy metabolism, and production of free radicals. Most of these molecular changes resolve spontaneously but, since cells are highly vulnerable, a second concussive event during this period of altered cell functions may have catastrophic consequences.